Phenol based redox mediators in electroanalysis - da Silva, Leonardo V.; de Almeida, Andresa K.A.; Xavier, Jadriane A.; Lopes, Cleylton B.; Silva, Francisco de Assis dos Santos; Lima, Phabyanno R.; dos Santos, Nicholas D.; Kubota, Lauro T.; Goulart, Marília O.F. (Journal of electroanalytical chemistry (Lausanne, Switzerland), 2018)
The building of chemically modified electrodes is attracting increasing interest over the past decades, with a large number of publications, in different applications. The present review focuses on a special class of surface modifiers based on activated phenols, which work as redox mediators, with most of the more recent materials applied in electroanalysis. Common remarks in this specific subject are reported, like the generation, on the majority of cases, of a reversible quinonoid redox system, able to mediate fast electron transfer toward a series of analytes, the use of carbon nanotubes and graphenes to avoid passivation and to obtain electroanalytical synergism. The steadily increasing number of examples of phenol-based redox catalysis demonstrates that the principle finds wide application in electroanalysis and related fields. This is, mainly, due to the fact that mediated processes frequently afford higher and/or different selectivity than a direct process. In addition, electrode reactions are accelerated and the overall energy consumption reduced, while reagent waste and difficult separation procedures can be avoided. Drawbacks in the area, like heterogeneity of surface, structural complexity of the phenol-based electrogenerated polymers/oligomers, doubts about covalent linkage or not to the surface modifiers, lixiviation, evaluation based on trial and error, are still present and need to be solved for a better and more efficient use of this kind of redox mediators. There is still a demand for more powerful characterization methods to eliminate experimental uncertainties. Electrochemical screening, using special devices, should be implemented in the area, to facilitate the choice of the best mediator. Rationalization based on computational/theoretical methods would help in terms of a well-designed phenol-structure directed to a special electroanalytical function. Schematic overview of significant parameters for phenol-based redox-mediators for a successful electroanalysis. A) Substrate; B) Surface modifier; C) Electrooxidized phenol-based mediator; D) Mediated reaction for electroanalysis. Cyclic voltammogram showing current increment in the presence of an analyte. [Display omitted] •Phenolic and polyphenolic antioxidants can be attractive for redox mediation.•Activated phenols work as redox mediators for electroanalysis.•Drawbacks concern heterogeneity of surface, difficulty on chemical structural definition and others.•Well-designed phenol-structure directed to a special electroanalytical function is needed.•Electrochemical screening should be implemented in the area.